Trends of frequency, mortality and risk factors among patients admitted with stroke from 2017 to 2019 to the medical ward at Kilimanjaro Christian Medical Centre hospital: a retrospective observational study - Stefan Siebert; Emma McIntosh; Blandina T Mmbaga; Kajiru Kilonzo; Baraka Moshi; Nateiya Yongolo; Sanjura Mandela Biswaro; Hans Maro; Sakanda Linus; William Nkenguye; Febronia Shirima; Rosalia E Njau; et al. (BMJ Open, 2023)
Objective The burden of stroke has increased in recent years worldwide, particularly in low-income and middle-income countries. In this study we aim to determine the number of stroke admissions, and associated comorbidities, at a referral hospital in Northern Tanzania.Design This was a retrospective observational study.Setting The study was conducted at a tertiary referral hospital, Kilimanjaro Christian Medical Centre (KCMC), in the orthern zone of Tanzania.Participants The study included adults aged 18 years and above, who were admitted to the medical wards from 2017 to 2019.Outcome The primary outcome was the proportion of patients who had a stroke admitted in the medical ward at KCMC and the secondary outcome was clinical outcome such as mortality.Methods We conducted a retrospective audit of medical records from 2017 to 2019 for adult patients admitted to the medical ward at KCMC. Data extracted included demographic characteristics, previous history of stroke and outcome of the admission. Factors associated with stroke were investigated using logistic regression.Results Among 7976 patients admitted between 2017 and 2019, 972 (12.2%) were patients who had a stroke. Trends show an increase in patients admitted with stroke over the 3 years with 222, 292 and 458 in 2017, 2018 and 2019, respectively. Of the patients who had a stroke, 568 (58.4%) had hypertension while 167 (17.2%) had diabetes mellitus. The proportion of admitted stroke patients aged 18–45 years, increased from 2017 (n=28, 3.4%) to 2019 (n=40, 4.3%). The in-hospital mortality related to stroke was 229 (23.6%) among 972 patients who had a stroke and female patients had 50% higher odds of death as compared with male patients (OR:1.5; CI 1.30 to 1.80).Conclusion The burden of stroke on individuals and health services is increasing over time, which reflects a lack of awareness on the cause of stroke and effective preventive measures. Prioritising interventions directed towards the reduction of non-communicable diseases and associated complications, such as stroke, is urgently needed.